Effects of Refractive Status and Axial Length of the Eye on Retinal Nerve Fiber Layer Thickness Measured by OCT - سليمان, يوسف; كردغلي, نجوى; ابراهيم, حنان (Latakia University Journal -Medical Sciences Series, 2020)
Aim: To evaluate the influence of refractive status and axial length of the eye on retinal nerve fibre layer thickness in emmetropics, mayopics and hyperopics.